2023
DOI: 10.32394/rpzh.2023.0250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental heat exposure on the health status in farmworkers, Nakhon Ratchasima, Thailand

Abstract: Background. Thailand is a tropical developing country which has a serious increase in health risk due to hot weather exposure among outdoor workers. Objectives. The aims of this study were to compare the factors related to environmental heat exposure in three different seasons, and to assess the relationship between environmental heat and dehydration status in each season among farmworkers in Nakhon Ratchasima, Thailand. Methods. A semi-longitudinal study was carried out in 22 male farmworkers throughout a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Meshi et al ( 11 ) conducted a cross-sectional study involving 60 miners working in extreme thermal environments and found that occupational setting in the mining area poses a significant risk of exposure to extreme heat conditions, which may contribute to the manifestation of symptoms related to heat-related illnesses. Sombatsawat et al ( 12 ) conducted a semi-longitudinal study involving 22 male farm employees working outdoors in hot weather throughout a year of farming. The study results indicated that farmworkers experienced significant exposure to environmental heat stress, which was manifested in physical changes.…”
Section: Introductionmentioning
confidence: 99%
“…Meshi et al ( 11 ) conducted a cross-sectional study involving 60 miners working in extreme thermal environments and found that occupational setting in the mining area poses a significant risk of exposure to extreme heat conditions, which may contribute to the manifestation of symptoms related to heat-related illnesses. Sombatsawat et al ( 12 ) conducted a semi-longitudinal study involving 22 male farm employees working outdoors in hot weather throughout a year of farming. The study results indicated that farmworkers experienced significant exposure to environmental heat stress, which was manifested in physical changes.…”
Section: Introductionmentioning
confidence: 99%